Manejo agroecológico y su efecto en la producción de banano (Musa x paradisiaca) en Ecuador - Sucad Buñay, Jorge Luis (2025)
In the development of the research based on "Agroecological management and its effect on banana production (Musa x paradisiaca) in Ecuador." In which the objective was to establish the effect of agroecological management on banana production (M. paradisiaca) in Ecuador. The methodology used was descriptive-analytical, with a qualitative approach, within its development the following topics were raised such as the generalities of banana cultivation, the geographical areas of production and predominant soils, the definition of agroecology, practices applicable in agroecological management to banana cultivation, influence of agroecological practices on the quality characteristics of the banana fruit and the impact of the application of organic amendments on the nutrition of the banana crop. Regarding the results, several agroecological management practices related to banana cultivation were recognized, which promote biodiversity in the agricultural system and reduce the appearance of pests. Agroecological practices influence the quality properties of bananas, improving both their appearance and internal characteristics. Finally, the use of organic amendments in banana cultivation has shown a notable effect on optimizing plant nutrition. Therefore, it is concluded that agroecological practices in banana cultivation significantly improve fruit productivity, thus improving agricultural sustainability. In addition, the application of organic amendments in soils not only improves soil capacity but also helps microbial activity and the root system of banana plants.